Analysis of elite road‐cycling sprints in relation to maximal power‐velocity‐endurance profile: a longitudinal one‐case study. (16th December 2021) - Robin, Maxime; Nordez, Antoine; Dorel, Sylvain
Abstract: The aims of the present study were to characterize the mechanical output of final road sprints of an elite sprinter during international competitions in relation to his power‐velocity‐endurance characteristics and to investigate the relationship between this sprint performance and the power produced during preceding phases of the race. The sprinter performed a set of short and long sprints (5 to 15‐s) on a cycle ergometer to determine his maximal power‐velocity‐endurance profile. Based on eleven races, the distribution of power throughout each race, peak and mean power ( Ppeak and Pmean ) and associated pedaling rates ( vPpeak and vPmean ) during the final sprint were analyzed. The power‐velocity‐endurance profile of the sprinter indicated that his theoeretical mean maximal power and corresponding optimal pedaling rate ranged from 20.0 W.kg −1 (124 rpm) for a 1‐s sprint to 15.0 W.kg −1 (109 rpm) for 20 s. Race data showed that final road sprints were mainly performed on the ascending limb of the power‐velocity relationship ( vPpeak, 104 ± 8 and vPmean, 101 ± 8 rpm). Additionally, Ppeak and Pmean were lower than the theoretical maximal power determined from the power‐velocity‐endurance profile (9.9 ± 7.0% and 10.6 ± 9.8%, respectively), which highlighted a significant state of fatigue induced by the race. Finally, sprint power exhibited a high variability between races and was strongly related to the level of power produced during the last minute before the sprint. These findings show the importance of considering both the power‐velocity‐endurance qualities and the power demand of the last lead‐up phase before the sprint in order to optimize final sprint performance.